Blending Cr2O3 into a NiO–Ni Electrocatalyst for Sustained Water Splitting. (24th August 2015) - Gong, Ming; Zhou, Wu; Kenney, Michael James; Kapusta, Rich; Cowley, Sam; Wu, Yingpeng; Lu, Bingan; Lin, Meng‐Chang; Wang, Di‐Yan; Yang, Jiang; Hwang, Bing‐Joe; Dai, Hongjie
Abstract The rising H2 economy demands active and durable electrocatalysts based on low‐cost, earth‐abundant materials for water electrolysis/photolysis. Here we report nanoscale Ni metal cores over‐coated by a Cr2O3‐blended NiO layer synthesized on metallic foam substrates. The Ni@NiO/Cr2O3 triphase material exhibits superior activity and stability similar to Pt for the hydrogen‐evolution reaction in basic solutions. The chemically stable Cr2O3 is crucial for preventing oxidation of the Ni core, maintaining abundant NiO/Ni interfaces as catalytically active sites in the heterostructure and thus imparting high stability to the hydrogen‐evolution catalyst. The highly active and stable electrocatalyst enables an alkaline electrolyzer operating at 20 mA cm−2 at a voltage lower than 1.5 V, lasting longer than 3 weeks without decay. The non‐precious metal catalysts afford a high efficiency of about 15 % for light‐driven water splitting using GaAs solar cells.